Individually optimized contrast‐enhanced 4D‐CT for radiotherapy simulation in pancreatic ductal adenocarcinoma. Issue 10 (23rd September 2016) - Choi, Wookjin; Xue, Ming; Lane, Barton F.; Kang, Min Kyu; Patel, Kruti; Regine, William F.; Klahr, Paul; Wang, Jiahui; Chen, Shifeng; D'Souza, Warren; Lu, Wei
Abstract : Purpose: To develop an individually optimized contrast‐enhanced (CE) 4D‐computed tomography (CT) for radiotherapy simulation in pancreatic ductal adenocarcinomas (PDA). Methods: Ten PDA patients were enrolled. Each underwent three CT scans: a 4D‐CT immediately following a CE 3D‐CT and an individually optimized CE 4D‐CT using test injection. Three physicians contoured the tumor and pancreatic tissues. Image quality scores, tumor volume, motion, tumor‐to‐pancreas contrast, and contrast‐to‐noise ratio (CNR) were compared in the three CTs. Interobserver variations were also evaluated in contouring the tumor using simultaneous truth and performance level estimation. Results: Average image quality scores for CE 3D‐CT and CE 4D‐CT were comparable (4.0 and 3.8, respectively; P = 0.082), and both were significantly better than that for 4D‐CT (2.6, P < 0.001). Tumor‐to‐pancreas contrast results were comparable in CE 3D‐CT and CE 4D‐CT (15.5 and 16.7 Hounsfield units (HU), respectively; P = 0.21), and the latter was significantly higher than in 4D‐CT (9.2 HU, P = 0.001). Image noise in CE 3D‐CT (12.5 HU) was significantly lower than in CE 4D‐CT (22.1 HU, P = 0.013) and 4D‐CT (19.4 HU, P = 0.009). CNRs were comparable in CE 3D‐CT and CE 4D‐CT (1.4 and 0.8, respectively; P = 0.42), and both were significantly better in 4D‐CT (0.6, P = 0.008 and 0.014). Mean tumor volumes were significantly smaller in CE 3D‐CT (29.8 cm 3, P = 0.03) and CE 4D‐CT (22.8 cm 3, P = 0.01) than in 4D‐CT (42.0 cm 3 ). Mean tumor motion was comparable in 4D‐CT and CE 4D‐CT (7.2 and 6.2 mm, P = 0.17). Interobserver variations were comparable in CE 3D‐CT and CE 4D‐CT (Jaccard index 66.0% and 61.9%, respectively) and were worse for 4D‐CT (55.6%) than CE 3D‐CT. Conclusions: CE 4D‐CT demonstrated characteristics comparable to CE 3D‐CT, with high potential for simultaneously delineating the tumor and quantifying tumor motion with a single scan.